2008
DOI: 10.1111/j.1365-3040.2008.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic interactions between algal symbionts and invertebrate hosts

Abstract: Some invertebrates have enlisted autotrophic unicellular algae to provide a competitive metabolic advantage in nutritionally demanding habitats. These symbioses exist primarily but not exclusively in shallow tropical oceanic waters where clear water and low nutrient levels provide maximal advantage to the association. Mostly, the endosymbiotic algae are localized in host cells surrounded by a host-derived membrane (symbiosome). This anatomy has required adaptation of the host biochemistry to allow transport of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
426
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 506 publications
(461 citation statements)
references
References 194 publications
(270 reference statements)
3
426
1
2
Order By: Relevance
“…It is possible then that the coral host maintains this concentration gradient in the areas surrounding symbiotic dinoflagellates by rapidly fixing ammonium into amino acids, which can be used by the coral or transferred to the algal cells later on. This hypothesis has been somehow neglected so far (but see : Miller and Yellowlees, 1989;Wang and Douglas, 1998;Yellowlees et al, 2008) based on evidence that GS/GOGAT cycle, the fastest route for incorporating ammonium into amino acids through glutamate, is not widespread in animals. However, recent studies demonstrated that GS/GOGAT cycle is active in several metazoans (Scaraffia et al, 2005;Hansen and Moran, 2011) and our analyses using BLAST algorithm (Altschul et al, 1990) indicate that transcripts encoding proteins with high similarities to the domains of GOGAT are present in two cnidarian genomes (Nematostella vectensis (Sullivan et al, 2006), genBank accession number: XP_001630774.1; Acropora digitifera (Shinzato et al, 2011), http://marinegenomics.oist.jp/acropora _digitifera/, gene ID: aug_v2a.08445.t1; Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible then that the coral host maintains this concentration gradient in the areas surrounding symbiotic dinoflagellates by rapidly fixing ammonium into amino acids, which can be used by the coral or transferred to the algal cells later on. This hypothesis has been somehow neglected so far (but see : Miller and Yellowlees, 1989;Wang and Douglas, 1998;Yellowlees et al, 2008) based on evidence that GS/GOGAT cycle, the fastest route for incorporating ammonium into amino acids through glutamate, is not widespread in animals. However, recent studies demonstrated that GS/GOGAT cycle is active in several metazoans (Scaraffia et al, 2005;Hansen and Moran, 2011) and our analyses using BLAST algorithm (Altschul et al, 1990) indicate that transcripts encoding proteins with high similarities to the domains of GOGAT are present in two cnidarian genomes (Nematostella vectensis (Sullivan et al, 2006), genBank accession number: XP_001630774.1; Acropora digitifera (Shinzato et al, 2011), http://marinegenomics.oist.jp/acropora _digitifera/, gene ID: aug_v2a.08445.t1; Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Together, the coral and their dinoflagellate partners are able to acquire inorganic nitrogen, which is advantageous in an environment where planktonic supply may be episodic (Yellowlees et al, 2008;Sheppard et al, 2009). Among the different dissolved nutrients, ammonium is the preferred source of nitrogen for symbiotic corals ( Figure 1a) (Grover et al, 2002(Grover et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterotrophy contributes most to the material needs (nitrogen compounds), while photoautotrophy contributes to the energy and carbon demand of the coral (Anthony and Fabricius 2000;Piniak et al 2003;Houlbrèque and Ferrier-Pagès 2008). The intense recycling and exchange of nutrients between the coral animal and the zooxanthellae make corals particularly adapted to life in nutrient-limited waters (Muscatine and Porter 1977;Furla et al 2005;Yellowlees et al 2008).…”
Section: Introductionmentioning
confidence: 99%